Expression Characterization of Six Genes Possibly Involved in Gonad Development for Stellate Sturgeon Individuals (Acipenser stellatus, Pallas 1771) - Alexandru Burcea; Gina-Oana Popa; Iulia Elena Florescu (Gune); Marilena Maereanu; Andreea Dudu; Sergiu Emil Georgescu; Marieta Costache (International Journal of Genomics)
Nowadays, in sturgeon’s aquaculture, there is a necessity for sex identification at early stages in order to increase the efficiency of this commercial activity. The basis for a correct identification is studying the different factors that influence the gonad development. The research has been directed towards molecular methods that have been employed with various degrees of success in identifying genes with different expression patterns between male and female sturgeons during their development stages. For the purpose of understanding the sexual development of 4-year-old stellate sturgeon (Acipenser stellatus) individuals, we have selected six genes (foxl2, cyp17a1, ar, dmrt1, sox9, and star). We analysed the gene expression of the selected genes for gonads, anal fin, liver, body kidney, and white muscle. The cyp17a1, ar, dmrt1, and sox9 genes have a significant higher expression in male gonads than in female gonads, while the data shows no significant differences in the expression of the investigated genes in the other organs. We investigate these genes to shed light on aquaculture sturgeon sexual development.